Evaluation of the Integration of the Traditional Architectural Element Mashrabiya into the Ventilation Strategy for Buildings in Hot Climates - Abdullah Abdulhameed Bagasi; John Kaiser Calautit; Abdullah Saeed Karban (Energies, 2021)
This paper reviewed related research works and developments on the traditional architectural element “mashrabiya” focusing on its history, design and structure, typology, and functions in hot climates. Moreover, the paper assessed the effect of the traditional mashrabiya on the indoor thermal environment and thermal comfort in a selected case study building. For this purpose, two similar rooms were investigated in a selected historic building with abundant mashrabiyas located in the Makkah Region, specifically in Old Jeddah, Saudi Arabia. The field tests were conducted during a typical hot summer month with two different configurations. The study demonstrated that opening the mashrabiya allowed more airflow into the room during the day and reduced the indoor temperature by up to 2.4 °C as compared to the closed mashrabiya. Besides, the building envelope played an important role in preventing the high fluctuation of the indoor air temperature, where the fluctuation of the rooms air temperature ranged between 2.1 °C and 4.2 °C compared to the outdoor temperature which recorded a fluctuation between 9.4 °C and 16 °C. The data presented here can be used for the future development of the mashrabiya concept and the potential incorporation with passive cooling methods to improve its design according to the requirements of modern buildings in hot climates. Moreover, further studies and tests on mashrabiyas under different climatic conditions are required. Also, the different strategies or materials can be incorporated with mashrabiyas in order to improve its thermal performance.